Promotion of Appel-type reactions by N-heterocyclic carbenes. Issue 55 (20th June 2019) - Hussein, Mohanad A.; Nguyen, Thanh Vinh
Abstract : N-Heterocyclic carbenes are found to mediate the Appel-type dehydrative halogenation reaction. Abstract : N-Heterocyclic carbenes (NHCs) have been extensively used as a versatile class of catalysts and ligands in organocatalytic and organometallic chemistry. However, there are only a small number of synthetic applications where they act as reagents. Here we demonstrate that NHCs can be used as stoichiometric redox reagents for Appel-type halogenation reactions of alcohols. This new reactivity reveals a fresh and interesting aspect and enriches the chemistry of NHCs in an underexplored area. The potential of performing this chemical transformation at the catalytic level using an NHC-oxide derivative is also investigated.